Electric Cardioversion in Older Adults. Is Sedation Using Propofol Safe in the Absence of the Direct Anesthetist's Assistance? - Jarosław Karwowski MD, PhD; Karol Wrzosek MD, PhD; Jerzy Rekosz MD, PhD; Katarzyna Tymoszuk MD; Anna Wiktorska MD, PhD; Katarzyna Szmarowska MD, PhD; Mateusz Solecki MD, PhD; Mirosław Dłużniewski MD, PhD (SAGE Publishing, 2024)
Aims: This study aimed to assess the safety of electric cardioversion in the absence of anesthetists assistance. We also evaluated the efficacy and safety of this procedure in older adults (≥80 years) compared to younger populations. Methods: We retrospectively analyzed the data of patients who underwent electric cardioversion at our cardiology department. Patients were divided into 2 groups according to age: ≥ 80 years and <80 years old. Results: The study included 218 participants, 73 were aged 80 years or more (mean age: 84.8 years), and 145 were younger than 80 years (mean age: 66.7 years). Electric cardioversion was effective in 97.3% of older patients and 96.5% of younger patients ( P  = 1.00). No thromboembolic complications were observed in either of the groups. Asystole >5 s occurred immediately after shock in 4.1% of older and 2.1% of younger patients ( P  = .405). Propofol was used as a sedative, with a mean dose of 0.83 mg/kg versus 0.93 mg/kg, in older and younger patients, respectively. Intubation, medical intervention, or other advanced resuscitation techniques were not required. During hospitalization, arrhythmia recurred in 9.6% and 12.4% of the older and younger patients, respectively ( P  = .537). Conclusions: Electrical cardioversion is an effective and safe procedure regardless of patient age. Sedation with propofol administered by cardiologists was safe. Adverse events were not considered serious or reversible.